The DEK oncoprotein is a Su(var) that is essential to heterochromatin integrity - Kappes, Ferdinand; Waldmann, Tanja; Mathew, Veena; Yu, Jindan; Zhang, Ling; Khodadoust, Michael S.; Chinnaiyan, Arul M.; Luger, Karolin; Erhardt, Sylvia; Schneider, Robert; Markovitz, David M. (Genes & development, 2011)
Heterochromatin integrity is crucial for genome stability and regulation of gene expression, but the factors involved in mammalian heterochromatin biology are only incompletely understood. Here we identify the oncoprotein DEK, an abundant nuclear protein with a previously enigmatic in vivo function, as a Suppressor of Variegation [Su(var)] that is crucial to global heterochromatin integrity. We show that DEK interacts directly with Heterochromatin Protein 1 α (HP1α) and markedly enhances its binding to trimethylated H3K9 (H3K9me3), which is key for maintaining heterochromatic regions. Loss of Dek in Drosophila leads to a Su(var) phenotype and global reduction in heterochromatin. Thus, these findings show that DEK is a key factor in maintaining the balance between heterochromatin and euchromatin in vivo.
Gesehen am 11.07.2022